Trimethoprim - Sulfamethoxazole in Combination With Meropenem Orpolymyxin is Effective in Management of Acinetobacter Baumannii Associated Pneumonia and Urinary Tract Infection - Keyal, Niraj Kumar; Nepal, Niru; Bhujel, Amid (Birat Journal of Health Sciences, 2020)
Acinetobacter baumanniiis a common multidrug resistant bacteria that causes pneumonia and urinary tract infection in intensive care unit and requires dual antibiotic for effective management. There are limited expensive antibiotics that are active against. Acinetobacter baumannii. Trimethoprim - Sulfamethoxazole is a cheap, older and easily available antibiotic that can be used in combination with Meropenem or Polymyxin for treatment to decrease antibiotic resistance. This case presentation of three patients describes the successful treatment of hospital acquired Pneumonia and Urinary Tract Infection by Acinetobacter baumannii with Trimethoprim - Sulfamethoxazole in combination with Meropenem and Polymyxin that lead avoidance of costly drugs and decrease in antibiotic resistance. Antibiotic resistance and lack of newer effective antibiotic against multidrug resistant bacteria like Acinetobacter baumannii is a common problem in intensive care unit. Trimethoprim -Sulfamethoxazole may help in combating this problem.